ENDOGAMY IN ISLAMIC BOARDING SCHOOL CARETAKER FAMILY: A MASLAHAH POINT OF VIEW - Kudrat Abdillah; Silmah Fathimiyah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Kyai and their family, as boarding school caretakers, become the leading role models in religious practice, including marriage. In Sumenep, Madura, some of these families practice endogamous marriage. This makes the assumption in society that the tradition of endogamous marriage continues to be preserved. This study aims to describe the endogamous marriage tradition in Boarding Schools in Sumenep from the perspective of al-Tufi’s Maslahah Theory. The researcher uses empirical legal research and case studies as his approach. The results show that the existing tradition of endogamous marriage is carried out by arranged marriage and is intended to safeguard assets, maintain lineage (nasab), and sustain the boarding school. According to al-Tufi’s Maslahah theory, the tradition has a beneficial value, although no al-Quran verses or hadith command endogamous marriage. The benefit is manifested in the goal for the continuity and development of education in the Islamic boarding school institution owned by the parents. However, there are negative impacts that need to be considered, such as hostility between families caused by unsuccessful matchmaking and the potential for abnormal or disabled children.